EXTH-28. INTRATUMORAL HETEROGENEITY OF THERAPEUTIC VULNERABILITIES ACROSS ENHANCING AND NON-ENHANCING TUMOR COMPONENTS OF GLIOBLASTOMA: A PARADIGM-SHIFTING PERSONALIZED MEDICINE APPROACH. (14th November 2022) - Lin, Wan-Hsin; Moniz-Garcia, Diogo; Feathers, Ryan; Brooks, Mieu; Middlebrooks, Erik; Kinsella, Lindsey; Chaichana, Kaisorn; Quiñones-Hinojosa, Alfredo; Anastasiadis, Panos
Abstract: Glioblastoma (GBM) is the most aggressive adult brain tumor with no effective therapy. Despite advances on its molecular characterization, targeted therapeutics remain out of reach. This lack-of-progress is largely attributed to molecular and spatial heterogeneity and absence of clinically applicable models to guide patient care. Moreover, as standard surgical resection is aimed at contrast-enhancing (CE) tumor, the molecular landscape and treatment response of the remaining non-contrast enhancing (nCE) component is largely unknown despite its active role in tumor progression and local recurrence. Here, we aimed to identify the functional impact of tumor heterogeneity and to explore therapeutic vulnerabilities of both CE and nCE components. Four tumor regions (two CE and two nCE) from each of five GBM patients were collected under neuronavigation. The resulting tissue was subjected to generation of 3D tumor models (a brain tumor initiating-enriched cell line and a spheroid-based mcancer model) with comparable success in both CE and nCE samples. A panel of 25 brain penetrant drugs (alone and in combination) targeting GBM drivers (i.e. RTK/Ras/PI3K, RB/cell cycle, p53/apoptosis, DNA damage repair, transcription addiction) was developed and used to test for therapeutic vulnerabilities. From each tumor region, 4.5 ± 3.7 (average ± SD) different targeting strategies were identified exhibiting at least 70% growth inhibition at Cmax. Drug response heterogeneity was relatively rare, varied among cases, and was independent of tumor enhancement status. To our knowledge, this is the first study to systemically assess treatment response from both CE and nCE patient-derived GBM models. Ongoing studies include comprehensive genome and transcriptome profiling and pathway analysis from these different tumor regions. We postulate that interrogation of molecular landscapes and vulnerability profiles of both CE and nCE tumor regions, will enable us to personalize and prioritize effective targeted interventions for GBM treatment.